Cerebral vasospasm patterns following aneurysmal subarachnoid hemorrhage: an angiographic study comparing coils with clips. (17th September 2014) - Jones, J; Sayre, J; Chang, R; Tian, J; Szeder, V; Gonzalez, N; Jahan, R; Vinuela, F; Duckwiler, G; Tateshima, S
Abstract : Background and purpose: Cerebral vasospasm following aneurysmal subarachnoid hemorrhage (aSAH) results in significant morbidity due to ischemia. Subarachnoid hematoma evacuation during aneurysm clipping reduces the incidence of vasospasm. However, studies comparing endovascular coiling with open clipping have reported similar rates of spasm. We addressed the question of how coiling produces similar (if not less) vasospasm without the benefit of clot evacuation by evaluating vasospasm patterns among patients with aSAH. We hypothesize that cerebrospinal fluid (CSF) circulation plays a major role in clearing blood breakdown products, and that coiling may preserve CSF flow in the subarachnoid space. Methods: A retrospective chart review identified 36 (18 coiled/18 clipped) patients with aSAH who developed angiographic vasospasm. The degree of spasm was quantified using an ordinal scale from 0 (none) to 5 (severe) for 26 anatomic vessel segments evaluated on 164 successive angiograms. Statistical analysis was performed using the Fisher exact test for proportions and the Wilcoxon and Student t tests on ordinal/continuous measures. Quadratic regression was also used as a model for spasm activity versus post-bleed days. Results: In both the coiling and clipping groups the most severely spastic vessels were located adjacent to aneurysm rupture. Perianeurysmal spasm affected all subjects. However, whereas spasm remained largely confined in patients treated by clipping, those who underwent coiling developed stepwise progression distally over time. The distal vasospasm severity scores were higher among subjects treated by coiling, particularly in the most dependent regions of the subarachnoid space. Conclusions: Patients with aSAH treated by endovascular coiling and surgical clipping demonstrate distinct vasospasm patterns. While both initially exhibit perianeurysmal spasm, patients treated by coiling go on to develop stepwise progression distally over time. This finding may reflect dispersion of blood breakdown products along preserved CSF egress pathways in patients treated by endovascular coiling.